Determinants of Dietary Diversity Practice among Pregnant Women in the Gurage Zone, Southern Ethiopia, 2021: Community-Based Cross-Sectional Study - Tolesa Gemeda Gudeta; Ayana Benti Terefe; Girma Teferi Mengistu; Seboka Abebe Sori (Hindawi Limited, 2022)
Background. Dietary diversification is considered the proxy indicator of dietary quality and nutrient adequacy during pregnancy. Pregnant women have been considered susceptible to malnutrition because of their increased nutrient demands and thus consuming a variety of foods in their diet plays a lion's role in ensuring adequate nutrient intake. So understanding bottleneck factors associated with dietary diversity practice is very crucial to encouraging adequate dietary diversity practice. Therefore, this paper aimed to assess determinants of dietary diversity practice among pregnant women in the Gurage zone, Southwest Ethiopia. Methods. A community-based cross-sectional analytical study was conducted among 726 pregnant women, 13 key informants, and 27 focus group discussion discussants in the Gurage zone, southwest Ethiopia, from 1 September to 1 November 2021. A face-to-face interviewer-administered questionnaire was used to collect the data. According to the Minimum Dietary Diversity Score for Women (MDD-W) tool, women who consumed more than or equal to 5 of 10 food groups in the previous 24 hours had a diverse diet. Epi data version 3.1 was used for data entry, while SPSSversion 26 was used for analysis. To determine factors associated with dietary diversity, bivariate and multivariable logistic regression models were used to obtain crude odds ratio (COR), adjusted odds ratios (AOR), and 95 percent confidence intervals (CIs). Statistical significance was determined using adjusted odds ratios (AORs) with 95 percent confidence intervals (CIs) and p values less than 0.05. In narrative form, qualitative results were triangulated with quantitative data. Results. The overall prevalence of the adequate dietary diversity practice was found to be 42.1% with 95% CI (48.4-46.1%) and the mean dietary diversity score was 5.30 ± 1.49 standard deviation (SD). Multivariable analysis revealed that primary school level [AOR = 6.471 (2.905, 12.415)], secondary school level (9-12) [AOR = 7.169 (4.001, 12.846)], college and above level [AOR = 32.27 (15.044, 69.221)], women with higher empowerment [AOR = 3.497 (2.301, 5.315)], women with a favorable attitude toward dietary diversity [AOR = 1.665 (1.095, 2.529)], women from wealthier households [AOR = 2.025 (1.252, 3.278)], and having well-secured food status [AOR = 3.216 (1.003, 10.308)] were variables that influence dietary diversity practice. Three FGD and 13 key informant interviews were conducted, and the results of qualitative data generated three major themes. Conclusion. The overall prevalence of adequate dietary diversity practice was found to be low in this study when compared to studies conducted in Ethiopia. Maternal educations, mothers' attitudes toward dietary diversity, women empowerment, food security status, and wealth index level of the household were determinant factors that influence dietary diversity practice in this study. Therefore, programs aimed to improve pregnant women's dietary diversity practice should focus on improving the socioeconomic status and creating a congenial environment to promote women's empowerment.